Fault Injection Attacks: Attack Methodologies, Injection Techniques and Protection Mechanisms - Bhasin, Shivam (2017)
Fault Injection Attacks are a powerful form of active attack mechanism which can threaten even the strongest of cryptographic algorithms. This attack vector has become more pertinent with the growing popularity of the Internet of things (IoT), which is based on small omnipresent embedded systems interacting with sensitive data of personal or critical nature. This tutorial addresses this issue of fault attacks, covering a wide range of topics which has accumulated through years of research. The first part of the talk will cover fault attacks and its application to attack standard cryptosystems. Different popular forms of fault attacks, namely Differential Fault Attacks (DFA) and Differential Fault Intensity Attacks (DFIA) are presented. It is followed subsequently by a discussion on the underlying injection techniques. Finally, protection mechanism will be discussed highlighting on information redundancy based reactive countermeasures and sensor-based protection mechanisms as two alternative strategies for security against the menacing fault attacks.